MAMP (microbe-associated molecular pattern)-induced changes in plasma membrane-associated proteins - Uhlíková, Hana; Solanský, Martin; Hrdinová, Vendula; Šedo, Ondrej; Kašparovský, Tomáš; Hejátko, Jan; Lochman, Jan (Journal of plant physiology, 2017)
Plant plasma membrane associated proteins play significant roles in Microbe-Associated Molecular Pattern (MAMP) mediated defence responses including signal transduction, membrane transport or energetic metabolism. To elucidate the dynamics of proteins associated with plasma membrane in response to cryptogein, a well-known MAMP of defence reaction secreted by the oomycete Phytophthora cryptogea, 2D-Blue Native/SDS gel electrophoresis of plasma membrane fractions was employed. This approach revealed 21 up- or down-regulated protein spots of which 15 were successfully identified as proteins related to transport through plasma membrane, vesicle trafficking, and metabolic enzymes including cytosolic NADP-malic enzyme and glutamine synthetase. Observed changes in proteins were also confirmed on transcriptional level by qRT-PCR analysis. In addition, a significantly decreased accumulation of transcripts observed after employment of a mutant variant of cryptogein Leu41Phe, exhibiting a conspicuous defect in induction of resistance, sustains the contribution of identified proteins in cryptogein-triggered cellular responses. Our data provide further evidence for dynamic MAMP-induced changes in plasma membrane associated proteins.
Keywords: Membrane Proteins; Cell Membrane; Plant Proteins; Fungal Proteins; rostlinné proteiny; Nicotiana; Pathogen-Associated Molecular Pattern Molecules; Chromatography, Liquid; Phytophthora; Tandem Mass Spectrometry; chromatografie kapalinová; tandemová hmotnostní spektrometrie; Trypsin; fungální proteiny; PAMP struktury; buněčná membrána; membránové proteiny; elektroforéza v polyakrylamidovém gelu; Electrophoresis, Polyacrylamide Gel; trypsin; tabák